1954
DOI: 10.1111/j.1365-2044.1954.tb01533.x
|View full text |Cite
|
Sign up to set email alerts
|

SUCCINYLDICHOLINE AND LIGNOCAINE BY CONTINUOUS INTRAVENOUS DRIP Report of 1000 administrations

Abstract: THE development of a technique utilising the short acting relaxant suxamethonium chloride (succinyldicholine chloride, Scoline) and the analgesic lignocaine hydrochloride (Xylocaine) followed the successful use of the combination gallamine and thi0pentone.l Scoline is an ultra short acting relaxant, and the length of action of a single dose appears to be intimately related to the level of serum cholinesterase of the recipient.2 3 4The administration of scoline by continuous intravenous drip was first described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1955
1955
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Three years later, De Clive-Lowe et al used intravenous lidocaine for the first time as adjuvant during general anesthesia. They showed that lidocaine provides post-operative analgesia with low incidence of post-operative nausea and vomiting [13]. Other studies showed that the use of lignocaine with thiopentone nitrous oxide-oxygen provide post-operative analgesia, low incidence of nausea and vomiting, and short recovery time without changes in pulse rate or blood pressure [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Three years later, De Clive-Lowe et al used intravenous lidocaine for the first time as adjuvant during general anesthesia. They showed that lidocaine provides post-operative analgesia with low incidence of post-operative nausea and vomiting [13]. Other studies showed that the use of lignocaine with thiopentone nitrous oxide-oxygen provide post-operative analgesia, low incidence of nausea and vomiting, and short recovery time without changes in pulse rate or blood pressure [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion is that a combination of a small dose of barbiturate with lidocaine is the most effective treatment for the temporary abolition of severe epileptic fits. In this way, also, excitatory effects of lidocaine, which have very rarely been observed after injection in man (Clive-Lowe, Gray, Spencer, and North, 1954), are avoided. SUMMARY 1.…”
Section: Discussionmentioning
confidence: 92%
“…Of the others lidocaine and diethoxine were the most potent. Since lidocaine seems to be less toxic than diethoxine and since, in addition, there is considerable evidence that the intravenous injection of lidocaine in man carries little risk of complications (Clive-Lowe, Gray, Spencer and North, 1954), lidocaine was the chief drug used in our further investigations on the central effects of local anaesthetics.…”
Section: Methodsmentioning
confidence: 99%
“…Three cases of convulsion were reported, and the authors emphasized the need for vigilance against toxicity. 54 Over the past 25 years, a number of randomized controlled trials (RCT) indicate that continuous intravenous lidocaine administration may have a beneficial effect on outcomes after colorectal surgery. 52,55 A recent meta-analysis of eight RCTs in patients undergoing colorectal surgery demonstrated a reduced duration of postoperative ileus, pain, nausea and vomiting, and shortened hospital stay with perioperative intravenous lidocaine administration.…”
Section: Use Of Intravenous Lidocaine Infusionsmentioning
confidence: 99%